2019
DOI: 10.1093/mnras/stz3278
|View full text |Cite
|
Sign up to set email alerts
|

Properties of reionization-era galaxies from JWST luminosity functions and 21-cm interferometry

Abstract: Next generation observatories will enable us to study the first billion years of our Universe in unprecedented detail. Foremost among these are 21-cm interferometry with the Hydrogen Epoch of Reionization Arrays (HERA) and the Square Kilometre Array (SKA), and high-z galaxy observations with the James Webb Space Telescope (JWST). Taking a basic galaxy model, in which we allow the star formation rates and ionizing escape fractions to have a power-law dependence on halo mass with an exponential turnover below so… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 88 publications
(96 reference statements)
4
23
0
Order By: Relevance
“…McGreer et al 2015;Planck Collaboration 2016;Pagano et al 2020). Furthermore, the galaxy scaling relations are consistent with results from hydrodynamic simulations (e.g., Xu et al 2016;Park et al 2020;Ma et al 2020) and semi-analytical galaxy formation models (e.g., Sun & Furlanetto 2016;Mutch et al 2016;Tacchella et al 2018;Behroozi et al 2019;Yung et al 2019). We briefly summarize the model here and its free parameters; interested readers can find more details in Park et al (2019).…”
Section: The Galaxy Modelsupporting
confidence: 71%
“…McGreer et al 2015;Planck Collaboration 2016;Pagano et al 2020). Furthermore, the galaxy scaling relations are consistent with results from hydrodynamic simulations (e.g., Xu et al 2016;Park et al 2020;Ma et al 2020) and semi-analytical galaxy formation models (e.g., Sun & Furlanetto 2016;Mutch et al 2016;Tacchella et al 2018;Behroozi et al 2019;Yung et al 2019). We briefly summarize the model here and its free parameters; interested readers can find more details in Park et al (2019).…”
Section: The Galaxy Modelsupporting
confidence: 71%
“…X-ray heating becomes relevant later (z 20, Cohen et al 2017Cohen et al , 2018 owing to the fact that it takes time for the first population of X-ray sources (such as X-ray binaries, Fragos et al 2013) to emerge. The impact of reionization on the 21-cm signal becomes apparent only at relatively late times (z 15 in Cohen et al 2017Cohen et al , 2018 with the appearance of massive galaxies which are efficient in ionizing the gas (e.g., Park et al 2020). It is, thus, expected that the Pop III-Pop II transition explored in this paper will mostly affect the 21-cm signal from the era of Ly-α coupling.…”
Section: Large-scale Simulations Of the 21-cm Signalmentioning
confidence: 80%
“…The assumption TK TCMB is a plausible approximation at redshifts of our interest, since heating due to X-rays from first sources is expected to raise temperature of the neutral gas well above the TCMB by z ∼ 10 ( Bowman et al 2018;Ghara et al 2021). Some recent models have suggested that X-ray heating might be delayed to z < 10 (Fialkov et al 2014;Madau & Fragos 2017;Mirocha et al 2017;Cohen et al 2017;Park et al 2020;Mebane et al 2020). Our assumption (TS TCMB) will not be valid in such scenarios, but other than the redshift of heating transition (TK TCMB), the spin temperature fluctuations are only expected to enhance the power spectrum of 21-cm signal (Fialkov et al 2014;Mesinger et al 2014;Raste & Sethi 2018Ma et al 2021).…”
Section: -Cm Signalmentioning
confidence: 98%